2019
DOI: 10.1063/1.5091682
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic correlation lengths in supercooled polymers

Abstract: A key point to understand the glass transition is the relationship between structural and dynamic behavior experienced by a glass former when it approaches Tg. In this work, the relaxation in a simple bead-spring polymer system in the supercooled regime near its glass transition temperature was investigated with molecular dynamic simulations. We develop a new manner to look at the dynamic length scales in a supercooled polymeric system, focusing on correlated motion of particles in an isoconfigurational ensemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Alternatively, by observing the behavior of incoherent intermediate scattering function, two relaxation mechanisms can be observed for temperatures below T A : the β at short times and the alpha at long times. From our previous work [39] it can be noted that both functions manifest the change in behaviour described above at a temperature close to T A . In what follows, we characterized the heterogeneous dynamics by two functions that are typically used to describe it.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Alternatively, by observing the behavior of incoherent intermediate scattering function, two relaxation mechanisms can be observed for temperatures below T A : the β at short times and the alpha at long times. From our previous work [39] it can be noted that both functions manifest the change in behaviour described above at a temperature close to T A . In what follows, we characterized the heterogeneous dynamics by two functions that are typically used to describe it.…”
Section: Resultssupporting
confidence: 62%
“…In previous works, we have have found, using ICEM, regions where the particles are strongly dynamically connected, as defined by a high value of Pearson's correlation coefficient; these particles also form clusters, but they are not the same than those formed by mobile or immobile particles [38]. In addition, we showed that a dynamic correlation length, defined from the decay of Pearson's correlation coefficient, shows a linear relation with a static correlation length in the whole temperature range, unlike typical fourpoint correlation lengths which display this linearity only for high temper atures [39].…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The prevailing methodology to detect spatial correlations in glassy systems is suggested by the random firstorder theory (RFOT) [8][9][10]: pinning a subset of particles in the equilibrium fluid, one examines how the configuration of the rest of particles is influenced [11][12][13][14][15]. While this point-to-set (PTS) protocol is designed to keep the static properties of the system in equilibrium, it represents a strong perturbation of the dynamics [16,17]: The freezing of some particles can be viewed as imposing a zero-temperature region and hence a strong temperature gradient, yet the associated linear-response regime shrinks to zero at the glass transition [18].…”
mentioning
confidence: 99%
“…The prevailing methodology to detect spatial correlations in glassy systems is suggested by the random first-order theory (RFOT) [10][11][12]: pinning a subset of particles in the equilibrium fluid, one examines how the configuration of the rest of particles is influenced [13][14][15][16]. While this point-to-set (PTS) protocol is designed to keep the static properties of the system in equilibrium, it represents a strong perturbation of the dynamics [17]:…”
mentioning
confidence: 99%